Habitação Social Sob A Perspectiva De Gênero: Conjunto Habitacional Carmen Portinho - Guimarães, Maria Júlia Carneiro De Souza (Universidade Federal do Tocantins, 2022)
The proposal of the Carmen Portinho Housing Estate arose from the interest in developing an inclusive architecture that meets the daily needs of women heads of household who live in the ARNOS region, in the city of Palmas TO. The research deals with the construction of an urban and housing space, more specifically a Social Interest Housing from a gender perspective, considering that the State and its public policies usually perpetuate machismo and misinformation in the way of designing and spreading urban and architectural characteristics, without taking into account the special needs of women who are mothers and have the role of providing and supporting the family. The research also analyzes the social class of this group, an essential factor to understand how these women live, what their reality is, and their demands. Collective housing was an intentional choice with the purpose of highlighting women, heads of families and, therefore, protagonists of the daily life of these places.